Detection and application of circulating tumor cell and circulating tumor DNA in the non-small cell lung cancer - Zhang, Yuting (Am J Cancer Res, 2018)
Non-small cell lung cancer (NSCLC) is the leading cause of cancer-related death in both men and women. The ability of cancer cells to break-off from the primary tumor and spread to distant organs is the main cause of death of cancer patients. The detection of circulating tumor cells (CTCs) and circulating tumor DNA (ctDNA) is a considerable part of liquid biopsy, which contributes to the diagnosis, treatment and prognosis, and especially to identify the targetable mutations of NSCLC. This review is to discuss the detection and application of CTC and ctDNA in the diagnosis, prognostic evaluation and guiding targeted therapy of NSCLC.